2017
DOI: 10.1002/jctb.5306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of embedded activated carbon nanoparticles on the performance of polydimethylsiloxane (PDMS) membrane for pervaporation separation of butanol

Abstract: BACKGROUND: The pervaporation separation method is considered to be a promising technique for biobutanol recovery from fermentation broths. In this work, activated carbon nanoparticles were embedded in polydimethylsiloxane (PDMS) membranes to improve the pervaporation performance. RESULTS: Adding 6 wt% nano-additives in PDMS membranes increased the flux and separation factor by 42.6% and 51.9%, respectively, compared with neat membranes at 37 ∘ C. Enhanced performance is due to: 1 the presence of additional so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 62 publications
0
32
1
Order By: Relevance
“…PDMS membrane showed a high separation factor, 154, which is one magnitude higher than similar works in the literature, varying from 9-40 4,19,22,23 . Probably this high selectivity is regarded to the use of a commercial glue instead of the usual PDMS kit.…”
Section: Activated Carbon Load Effectmentioning
confidence: 60%
See 2 more Smart Citations
“…PDMS membrane showed a high separation factor, 154, which is one magnitude higher than similar works in the literature, varying from 9-40 4,19,22,23 . Probably this high selectivity is regarded to the use of a commercial glue instead of the usual PDMS kit.…”
Section: Activated Carbon Load Effectmentioning
confidence: 60%
“…They concluded that the addition of activated carbon caused a decrease in 50% on the energetic barrier for the alcohol transport. On the other hand, Azimi and coworkers 19 found activation energy of 66.4 and 43.9 kJ/ mol for butanol and water, respectively, in the permeation of binary solutions to activated carbon-loaded PDMS, leading to the conclusion that butanol permeation is more susceptible to temperature changes. However, although water has the highest apparent activation energy in this work and the lower affinity to PDMS, it showed the highest flux since it is the smaller specie and its concentration in feed is the highest one (higher driven force for transport) 22,23 .…”
Section: Temperature Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The flux is the permeate flow per unit membrane surface area and per unit time, which is normally determined for each species from the individual permeation flow rates. [26][27][28]…”
Section: Pervaporation Experimentsmentioning
confidence: 99%
“…The validation of the extended RB model was performed using experimental data obtained in our laboratory for the pervaporation separation of butanol from aqueous binary solutions using a PDMS/Super Activated Carbon Powder membrane [10]. Fig.…”
Section: Model Validationmentioning
confidence: 99%